Pengaruh Syariah Marketing, Service Excellence dan Reputasi Terhadap Kepercayaan Nasabah Tentang Tabungan Emas: Studi Kasus Bank Syariah Indonesia KCP Panyabungan - Nur Ainun Ningsih; Tuti Anggraini; Nurul Jannah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study aims to determine the Influence of Sharia Marketing, Service Excellence, and Reputation on Customer Trust About Gold Savings (Case Study of Bank Syariah Indonesia KCP Panyabungan) both partially and simultaneously. The population in this study is all customers at Bank Syariah Indonesia KCP Panyabungan while the sample in this study is 100 customers. This study used quantitative methods with data collection using Likert scale method. Data analysis techniques through the IBM SPSS statistical 25 program. The results of research and discussion, several conclusions can be drawn as follows: Sharia Marketing affects Customer Trust About Gold Savings (Case Study of Bank Syariah Indonesia KCP Panyabungan), Service Excellence affects Customer Trust About Gold Savings (Case Study of Bank Syariah Indone Indonesia KCP Panyabungan), Reputation affects Customer Trust About Gold Savings (Case Study of Bank Syariah Indonesia KCP Panyabungan) and Sharia Marketing, Service Excellence, and Reputation on Customer Trust About Gold Savings (Case Study of Bank Syariah Indonesia KCP Panyabungan).